Review on the Study of Monsoon-Westerly Interaction in the Inland Arid Zone of Northwestern China - Shengchun XIAO; Jingrong SU; Xiaomei PENG; Quanyan TIAN (Gaoyuan qixiang)
The inland arid zone of northwestern China has two climate regimes， monsoon-dominated and westerly-dominated， and is also an area of monsoon-westerly interaction.The study of climate and environment in this region is of great theoretical and practical significance， and it is also a frontier issue that has attracted much attention in global change research.This paper summarized the research progress on the definition of the monsoon zone， the westerly belt and their boundary zones， the progress on the climatic impacts of these two circulations and their interactions as indicated by instrumental measurements and proxies.Future research needs to focus on the westerly-dominated climate regime and its interaction with the monsoon， spatial definition， and driving mechanisms at high resolution and large spatial and temporal scales.These studies can promote research on the response to global change and its dynamic mechanism， and provide scientific support and theoretical basis for regional desertification management and national ecological security guarantee in arid northwestern China.